Effect of San'ao decoction with scorpio and bombyx batryticatus on CVA mice model via airway inflammation and regulation of TRPA1/TRPV1/TRPV5 channels. (10th January 2021) - Wang, Pengli; Shang, Erxin; Fan, Xinsheng
Abstract: Ethnopharmacological relevance: Cough variant asthma (CVA) is characterized with its long-lasting cough symptom on clinic. The mechanism of CVA is related to chronic persistent airway inflammation, airway hyperresponsiveness, etc. The traditional Chinese prescription has achieved good curative effect on CVA treatment through reducing cough counts, decreasing airway hyperresponsiveness and alleviating airway inflammation. The mechanism is associated with reducing IL4, IL-13, NGF and CGRP levels, as well as down-regulating TRPA1/TRPV1/TRPV5 channels in both lung and brain tissues. Aim of the study: The Chinese prescription, San'ao decoction with scorpio and bombyx batryticatus (SSB), is well known in treating cough in asthmatic patients. In this study, the anti-tussive and anti-asthmatic role of SSB, as well as its mechanism on CVA mice model were explored and evaluated via alleviating airway inflammation and regulation of TRP channels. Materials and methods: The major chemical components in SSB were detected and analyzed by UPLC-QTOF-MS under an optimized chromatographic and MS condition. 60 BALB/c mice were randomly divided into six groups: normal group, model group, dexamethasone group (0.1178 mg/kg/d), SSB high dose group (9.74 g/kg/d), SSB middle dose group (4.87 g/kg/d) and SSB low dose group (2.435 g/kg/d). The cough variant asthma mice model was established by ovalbumin sensitization and challenge. The protective role of SSB on CVA mice model was studied through inducing cough counts by capsaicin, assessing inflammatory cells in peripheral blood and bronchoalveolar lavage fluid (BALF), measuring airway responsiveness, detecting histopathological changes in lung tissues, analyzing cytokines and neuropeptides levels in BALF, as well as examining the mRNA and protein expressions of TRPA1, TRPV1 and TRPV5 in both lung and brain tissues. Results: 17 signal peaks of the chemical components in SSB were identified by using UPLC-QTOF-MS. SSB (especially the high dose and middle dose), showed significantly effects on mice model by reducing mice cough counts (P ＜ 0.01), decreasing eosinophil (EOS) counts in blood (P ＜ 0.01) and inflammatory cell numbers in BALF (P ＜ 0.01), decreasing airway hyperresponsiveness (P ＜ 0.05), reducing the levels of IL-4 (P ＜ 0.05), IL-13 (P ＜ 0.01), NGF (P ＜ 0.01) and CGRP (P ＜ 0.01) in BALF, as well as down regulating the mRNA and protein expressions of TRPA1, TRPV1 and TRPV5 in both lung and brain tissues (P ＜ 0.01). Conclusions: SSB showed anti-tussive and anti-asthmatic effects on cough variant asthma mice model by reducing cough counts, improving lung function, alleviating lung injury and airway inflammation. The mechanism of SSB might be associated with the regulation of cytokines and neuropeptides in BALF, as well as the regulation of TRPA1, TRPV1, TRPV5 channels in both lung and brain tissues. Graphical abstract: Image 1